Patterns in the use of medicines by university students in Maputo, Mozambique Padrão de utilização de medicamentos por estudantes de uma universidade de Maputo, Moçambique - Raquel Lucas; Nuno Lunet; Rui Carvalho; Júlio Langa; Marília Muanantatha; Lucien-Pierre Nkunda; Henrique Barros (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2007)
Patterns in the use of medicines are expected to reflect distinct health features between populations. This study aimed to describe the self-reported use of medication by a sample of university students in Maputo, Mozambique. We conducted a survey of 797 students in a private university in Maputo. Participants completed a questionnaire including socio-demographic data and pattern of medication use in the preceding month. Information was collected on the number and names of drugs, duration of use, and prescription. The drugs were grouped according to therapeutic indication. In the previous month, 56% of students had used at least one pharmaceutical drug, with higher prevalence for women (65.2% vs. 42.2%) and men attending health-related courses (67.4% vs. 53.2%). The most commonly used medicines were anti-inflammatory/analgesic drugs (62.2%), anti-infectives (25.9%), and vitamins/minerals (13.6%). The most frequently used single drugs were paracetamol (42.8%), amoxicillin (12.6%), and ibuprofen (8.4%). Duration of use was lowest for anti-inflammatory/analgesic drugs and highest for oral contraceptives. Use of medication by Mozambican students was similar to that observed in other university populations. O padrão de utilização de medicamentos nas populações pode refletir diferenças na sua saúde. O objetivo deste estudo foi descrever o uso de medicamentos numa população universitária em Maputo, Moçambique. Foram avaliados 797 estudantes de uma universidade privada. Os participantes preencheram um questionário que incluía variáveis sócio-demográficas e de utilização de medicamentos no mês anterior. Foi colhida informação relativa ao número e nome dos medicamentos, duração da utilização e prescrição. Os fármacos foram classificados conforme a indicação terapêutica. Entre os estudantes, 56% tinham utilizado pelo menos um fármaco, com maior prevalência nas mulheres (65,2% vs. 42,2%) e nos homens que freqüentavam cursos de saúde (67,4% vs. 53,2%). Os estudantes usaram principalmente antiinflamatórios/analgésicos (62,2%), anti-infecciosos (25,9%) e vitaminas/minerais (13,6%). Os fármacos mais freqüentemente utilizados foram paracetamol (42,8%), amoxicilina (12,6%) e ibuprofeno (8,4%). A duração da terapêutica foi menor para antiinflamatórios/analgésicos e maior para contraceptivos orais. O padrão de utilização de medicamentos por estudantes moçambicanos foi semelhante ao observado noutras populações universitárias.